A Ocupação Vista Alegre do Juá no contexto da produção do espaço urbano em Santarém (PA) - PINHO, Erick Rodrigo Porto (Universidade Federal do Oeste do Pará, 2024)
The present work has as its theme the production of urban space in Santarém, based on a study in the Ocupação Vista Alegre do Juá. With the objective of describing how the resident of the Vista Alegre do Juá occupation took place in the context of the production of urban space in Santarém/PA. The municipality of Santarém was initially configured from the relationships that developed with the river throughout its historical formation process. In recent decades, the city has experienced the expansion of the agricultural frontier and has been transformed according to the dynamics of real estate capital. This has increasingly caused the appreciation of urban space, guaranteed for the peripherization and the involvement of urban occupations in the municipality. It consists of a descriptive, bibliographical and field research, using qualitative data analysis techniques. As a result, it can be understood that there is an excluding logic of production of urban space of which the Vista Alegre do Juá occupation, like the other existing ones, is a consequence. Thus, it is necessary that the housing policies of the municipality be effective in the sense of regular occupation of space, minimize the housing deficit and ensure that the low-income population can have access to housing through formal means.